Municipal Capacity to Respond to COVID-19: Implications for Improving Community Resilience in Maine - Levesque, Vanessa; Johnson, Eileen; Bell, Kathleen (Maine Policy Review, 2021)
The authors of this article explore how 50 Maine municipalities communicated their response to COVID-19 in the earliest stages of the pandemic. The study answers two questions: (1) What information and resources did Maine municipalities communicate about COVID-19? and (2) What characterizes a more robust communication response? Analyzing digital communications from March through July 2020, the authors found almost all municipalities in our sample communicated basic information about altered town operations. Some towns provided more robust responses that evolved over time and included nuanced messages about COVID-19, a sense of community, and collaborations with partners. While smaller, more rural municipalities may have fewer residents and resources, many showed a larger-than-expected capacity to pivot quickly and rally together to respond to COVID-19 and communicate about that response.
Keywords: community resilience; municipal resilience; economic development; social capital; communication